2013
DOI: 10.1039/c2cc36356a
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D photoreactive lanthanide MOFs of trans,trans-muconic acid

Abstract: Three 2D and 3D photoreactive MOFs of trans,trans-muconic acid with Er(3+) and their corresponding isomorphous Y(3+) phases were synthesized and their photoreactivity was studied as a function of the crystal environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Such molecular movements during the photodimerization of olefins have been observed before. 7 Similarly, [ZnBr 2 (2F-4spy) 2 ] ( 4) is found to be isomorphous and isostructural to 1 and also showed SCSC dimerization due to the formation of cyclobutane rings between two monomers through [2+2] cycloaddition reaction to [Zn 2 Br 4 (rctt-F-ppcb)-(2F-4spy) 2 ] (5) (where rctt-F-ppcb = rctt-1,3-bis(4 0 -pyridyl)-2, 4-bis(2-fluoro-phenyl)cyclobutane) under UV light in 24 h. As seen from Fig. 3, the photoreactivity of ground powder of 4 dramatically increased compared to 1 such that 80% conversion of CQC bonds to the cyclobutane ring occurs just within 2 h. In other words, the reaction did not stop upon the formation of the dimer, when 4 was ground to a powder using a pestle and a mortar.…”
mentioning
confidence: 99%
“…Such molecular movements during the photodimerization of olefins have been observed before. 7 Similarly, [ZnBr 2 (2F-4spy) 2 ] ( 4) is found to be isomorphous and isostructural to 1 and also showed SCSC dimerization due to the formation of cyclobutane rings between two monomers through [2+2] cycloaddition reaction to [Zn 2 Br 4 (rctt-F-ppcb)-(2F-4spy) 2 ] (5) (where rctt-F-ppcb = rctt-1,3-bis(4 0 -pyridyl)-2, 4-bis(2-fluoro-phenyl)cyclobutane) under UV light in 24 h. As seen from Fig. 3, the photoreactivity of ground powder of 4 dramatically increased compared to 1 such that 80% conversion of CQC bonds to the cyclobutane ring occurs just within 2 h. In other words, the reaction did not stop upon the formation of the dimer, when 4 was ground to a powder using a pestle and a mortar.…”
mentioning
confidence: 99%
“…This may be due to the generation of the stress created during the photoreaction, the single crystals were collapsed after 55% photoreaction [61]. Similarly, isomorphs of the above structures have also been investigated by the same authors [62]. In all these compounds, the separation distance between the olefin bonds varies from 3.7 to 4.4 Å and also not aligned in parallel.…”
Section: Cis-trans Isomerization On the Gas Adsorption Property Of Mofsmentioning
confidence: 95%
“…The rate constants obtained from these curves were 5.4 × 10 −2 s −1 for the region 1630-1603 cm −1 and 4.3 × 10 −2 s −1 for the region 1025-980 cm −1 . Considering that the error associated with this methodology does not exceed 15%, 8 the two values are practically equal.…”
Section: Photochemical Reactivitymentioning
confidence: 98%
“…7 Another way of comparing the photoreactivity of the same molecule in various crystal environments is to construct metal-organic frameworks (MOFs) using potentially photoreactive organic molecules as ligands. 8,9 Moreover, in the case of isomorphous MOFs, this approach allows comparison of the photoreactivity of a molecule in almost identical crystal environments, the only difference being small variations in the geometry of neighboring olefinic bonds. By comparing the reaction rates of isomorphous MOFs of trans,trans-muconic acid we showed that the nature of the metal also affects the reaction rate probably via ligand-tometal energy transfer.…”
Section: Introductionmentioning
confidence: 99%